2022
DOI: 10.1590/0034-7167-2021-0214
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding booklet in prison institutions: initiative for promotion, protection and support

Abstract: Objectives: to understand the use of the booklet on breastfeeding in prison in times of COVID 19 by managers and health professionals who work with pregnant and breastfeeding women deprived of their liberty. Methods: this is a descriptive, exploratory research with a qualitative approach, carried out from March to December 2020. Thirteen professionals who work in Brazilian prison institutions participated in the study and answered a semi-structured interview. The data obtained were submitted to content analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Despite findings on the high participation of imprisoned mothers in educational activities developed by nurses on breastfeeding (90%) (Cavalcanti et al, 2018), Guimarães et al (2018) highlighted the stressful effects of authoritarian rules imposed by the prison system that reduce the decision-making power of breastfeeding women and increase their resistance to implementing strategies. Still, the exploratory research by Santos et al (2022c) concluded that, for managers and health professionals from several Brazilian states, a booklet on breastfeeding in prison proved to be a tool that strengthens the practice, guaranteeing rights, alleviating anxieties, and valuing breastfeeding women, in addition to reaching family members with relevant information.…”
Section: Critical Analysis Of Brazilian Production On the Practice Of...mentioning
confidence: 99%
“…Despite findings on the high participation of imprisoned mothers in educational activities developed by nurses on breastfeeding (90%) (Cavalcanti et al, 2018), Guimarães et al (2018) highlighted the stressful effects of authoritarian rules imposed by the prison system that reduce the decision-making power of breastfeeding women and increase their resistance to implementing strategies. Still, the exploratory research by Santos et al (2022c) concluded that, for managers and health professionals from several Brazilian states, a booklet on breastfeeding in prison proved to be a tool that strengthens the practice, guaranteeing rights, alleviating anxieties, and valuing breastfeeding women, in addition to reaching family members with relevant information.…”
Section: Critical Analysis Of Brazilian Production On the Practice Of...mentioning
confidence: 99%
“…47 Studies continue to advance in the area of COVID-19 immunization for pregnant women, although many have chosen not to be vaccinated, even so, there has been a reduction in mortality from COVID-19 infection in this group. [47][48][49][50]…”
Section: Potential Developed In the Covid-19 Pandemic For Pregnant An...mentioning
confidence: 99%
“…22,49 A national study carried out by the neonatology team created and validated a booklet for pregnant women with the main information on breastfeeding in times of COVID-19. 31,38,50 The booklet is a strategy that can be useful in health education, but we must pay attention to those women who are illiterate or functionally illiterate, and those who have a disability or visual limitation.…”
Section: Understand How To Continue Educating Women About Breastfeedi...mentioning
confidence: 99%
See 1 more Smart Citation